(untitled) (Journal of Parents and Teachers, 2014)
With his think, Freud helps us to establish at least one of the senses that the word ’educate’ can have: to provide the conditions of possibility for the development of the child´s subjectivity, allowing their inclusion in the culture and the social bond. On the other hand he shows us that the process is filled with paradoxes, in which the unconscious factors are determinant and the perfection is conspicuous by her absence.